Business intelligence systems and bank performance in Ghana: The balanced scorecard approach - Acheampong Owusu (Taylor & Francis Group, 2017)
Business intelligence (BI) systems has been widely publicised as providing immense benefits to organisations that have implemented it. Yet, very few studies have empirically evaluated these assertions theoretically. The main aim of this study is to empirically evaluate the impacts of adopting BI systems on organisational performance of banks. A conceptual model was developed using the balanced scorecard. Data were collected through hand-administered survey questionnaires from the universal banks in Ghana where 130 samples from executives were analysed through partial least squares structural equation modelling (PLS-SEM). The results indicate that BI Systems indeed have a positive significant effect on the learning and growth, internal process and customer performances of the banks. However, the findings proved that the adoption of BI systems does not directly lead to the financial performance of the banks, but rather through the indirect effects of learning and growth, internal process and customer performances thus confirming the core premise of the balanced scorecard. A major practical implication from the study is that vendors can capitalise on the findings to promote their BI products.